Kawasaki disease - characteristics, diagnosis, and management - Yevheniia Popravko; Nikola Siekierko; Wiktoria Kotusiewicz; Mateusz Lewandowski; Maja Żołnierek; Zuzanna Lubczyńska; Jakub Świętochowski; Grzegorz Bienia (Termedia Publishing House, 2024)
Kawasaki disease (KD) is an acute systemic vasculitis of medium - sized vessels that affects infants and children. The etiology of KD is unclear. Typical KD requires the presence of fever of at least 5 days duration and coexisting ≥ 4/5 principal clinical features: bilateral bulbar conjunctival injection, erythema and cracking og lips, skin rash, erythema and edema of the palms and feet, unilateral cervical nonpurulent lymphadenopathy. If patient presents less than 4 of the principal clinical features, the diagnosis of incomplete KD should be considered. The basis of initiate treatment of KD is a single dose of intravenous immunoglobulin (IVIG) with acetylsalicylic acid. But about 10-20% of patients do not respond to IVIG-therapy. Timely and adequate treatment of KD by IVIG and aspirin could help to prevent the development of coronary artery lesions, thats why diagnosis of KD is very important.